2019
DOI: 10.3390/ijms20133117
|View full text |Cite
|
Sign up to set email alerts
|

Dual Role of Metallic Trace Elements in Stress Biology—From Negative to Beneficial Impact on Plants

Abstract: Heavy metals are an interesting group of trace elements (TEs). Some of them are minutely required for normal plant growth and development, while others have unknown biological actions. They may cause injury when they are applied in an elevated concentration, regardless of the importance for the plant functioning. On the other hand, their application may help to alleviate various abiotic stresses. In this review, both the deleterious and beneficial effects of metallic trace elements from their uptake by roots a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(52 citation statements)
references
References 163 publications
(231 reference statements)
4
47
0
1
Order By: Relevance
“…In this research, the increase of Zn content was recorded only in tarragon and lavender treated with AMF. A recent investigation of Muszýnska and Labudda [43] showed the ability of Zn to enhance plant tolerance to abiotic stress, which may be partially connected with the increase in stress tolerance of AMF-treated A. dracunculus compared to L. angustifolia and H. officinalis in the present investigation. Interestingly, the concentration of two other natural antioxidants, such as iodine and selenium, significantly increased in AMF-inoculated A. dracunculus plants, showing the highest tolerance to abiotic stress as shown by biochemical analysis ( Table 5).…”
Section: Growth Conditions and Experimental Protocolsupporting
confidence: 66%
“…In this research, the increase of Zn content was recorded only in tarragon and lavender treated with AMF. A recent investigation of Muszýnska and Labudda [43] showed the ability of Zn to enhance plant tolerance to abiotic stress, which may be partially connected with the increase in stress tolerance of AMF-treated A. dracunculus compared to L. angustifolia and H. officinalis in the present investigation. Interestingly, the concentration of two other natural antioxidants, such as iodine and selenium, significantly increased in AMF-inoculated A. dracunculus plants, showing the highest tolerance to abiotic stress as shown by biochemical analysis ( Table 5).…”
Section: Growth Conditions and Experimental Protocolsupporting
confidence: 66%
“…Ban et al [68] showed that a low dose of Pb stimulated growth, the photosynthetic rate, transpiration and stomatal conductance in corn. In the shoots of many plant species, the hormesis that is caused by Cd is associated with an increase in the photosynthesis activity, which improves plant development [4,41]. In our study, the hormetic stimulation of growth that was caused by Pb was correlated with increased photosynthetic and transpiration rates, while the hormetic stimulation of growth that was caused by Cd led to a significant decrease of all of the investigated plant gas exchange parameters (Figure 7).…”
Section: Discussionsupporting
confidence: 48%
“…We would like to stress that an increase in the IAA and flavonol content have been proposed as the key factors in hormesis here for the first time. In general, the literature on metals and hormesis is dominated by studies on the role of oxidative stress and phytohormones such as abscisic acid, ethylene or jasmonates, with little information on the role of IAA and flavonols [3,4,6,41,54]. The results presented here also suggest that an increase in the photosynthesis and transpiration rates are not necessary for stimulating hormetic growth.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…We studied the combined effect of 10 ionic liquids (ILs) on luciferase, and observed that their mixtures presented a higher inhibitory effect, when all ILs components were in their maximum stimulatory effect concentration [11]. Therefore, the beneficial effects [12] in hormesis should be evaluated in the context of mixtures.…”
Section: Introductionmentioning
confidence: 99%